Counterfactual Thinking-Related Emotional Responses in Patients With Major Depressive Disorder - Zheng, Qi; Liao, Mei; Liu, Bangshan; Ou, WenWen; Chen, WenTao; Liu, Jin; Zhang, Yan (Frontiers in Psychiatry, 2021)
Objective: To explore the emotional characteristics of counterfactual thinking (CT)-related emotion responses in patients with major depressive disorder (MDD) via the “counterfactual thinking gambling task (CTGT).” Method: Twenty-five patients with MDD (the MDD group) and twenty-five healthy controls (the HC group) with matched demographic features were included. The 17-item Hamilton Depression Scale (HAMD) and the 14-item Hamilton Anxiety Rating Scale (HAMA) were used to assess the severity of depression and anxiety symptoms. The counterfactual thinking gambling task was applied to assess the situation-focused- and behavior-focused-CT-related emotion responses in the MDD group and the HC group. Results: There was no significant difference in general demographic data between the two groups (p > 0.05). Compared with the HC group, the MDD group experienced higher levels of “disappointment” and lower levels of “joy” in the situation-focused CT paradigm (p < 0.05). However, the experience of “regret” and “relief” in the behavior-focused CT paradigm were not significantly different between the two groups (p > 0.05). Conclusions: MDD is associated with an impaired situation-focused-CT-related emotion responses, and is often accompanied by increased disappointment and decreased joy; however, behavior-focused-CT-related emotion responses are not significantly affected in MDD. This pattern may represent the characteristic CT-related emotion responses of MDD.